Next-generation sequencing based mutation profiling reveals heterogeneity of clinical response and resistance to osimertinib. (March 2020) - Zhao, Jun; Lin, Gen; Zhuo, Minglei; Fan, Zaiwen; Miao, Liyun; Chen, Likun; Zeng, Aiping; Yin, Rong; Ou, Yangming; Shi, Zhihui; Yin, Jie; Gao, Wen; et al.
Highlights: Parallel evolution converging on EGFR resistant mutations, C797S/G. Gain-of-function mutations of CTNNB1 were highly enriched in our cohort. Concurrent genomic landscape plays an important role in osimertinib resistance. TP53 inactivating mutations negatively affect patients' duration of treatment. The importance of NGS based genetic profiling in the era of precision medicine. Abstract: Objectives: The 3rd generation epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR TKI) osimertinib has shown promising efficacy both in EGFR-mutant, T790M positive non-small cell lung cancer (NSCLC) patients who have become resistant to 1st or 2nd generation EGFR TKIs and patients with sensitizing EGFR mutations as the first line therapy. However, the degree and duration of response to osimertinib are heterogeneous. We hypothesized that the concurrent genomic landscape of these tumors could play a role in clinical outcomes and/or mechanisms of resistance. Materials and methods: We conducted a retrospective multicenter study of lung cancer patients who had developed resistance to osimertinib. Genomic profiling was done for all the patients by using targeted next-generation sequencing encompassing 59–1021 cancer-related genes. Results and conclusion: Known EGFR -dependent resistant mutations and activation of alternative pathways were identified in 44 % of all the patients with great heterogeneity. Gain-of-function mutations of CTNNB1 were highly enriched in our cohort. Some other putative resistance mechanisms to osimertinib, such as the recurrent EGFR V834 L mutation, were also identified. Moreover, pathogenic mutations of TP53 were negatively related to the efficacy of osimertinib. To sum up, heterogeneity of resistance to osimertinib was not only manifested by inter-individual differences, but also embodied in its intra-individual diversity.